On the Effect of Positive Curriculum on Distress and Attainment of Iranian Dorm-Living Students: Incorporating Religious Counseling - Farokhipour, Sajjad; Khoshnoudi, Hadi; Rezai, Afsheen; Mostafapour, Ehsan (Iranian Journal of Educational Sociology, 2022)
Purpose: Considering rich theoretical underpinnings of positive psychology (PP), the current study aimed to investigate the effects of an extra educational curriculum on the basis of PP on distress and attainment of Iranian high school students who are living in dormitories in boarding schools. Methodology: This is an empirical study with a post-test only control group design in which a sample of 346 male students were selected through convenience sampling from two boarding schools in Qom city during 2018-2019. A translated and validated version of K10 distress questionnaire (Kessler et al, 2010) was administered to them and 67 students with high distress symptoms were identified and randomly allocated to a control group (N=23), experimental group one (N= 22) and experimental group two (N=22). First, the experimental group underwent 16 sessions (twice a week for 90 minutes) of PP curriculum integrated with religious counseling. Employing a post-test only control-group design, the group’s performance on a distress scale (Goldberg, 1981) and their mean scores were compared after the intervention. Kruskal-Wallis and ANOVA tests were used to compare differences between the groups. Findings: Findings revealed that positive curriculum alleviated distress symptoms of the experimental groups vis-à-vis the control (χ2 (2) = 52.851, p ≤ 0.001). Also, to investigate the effect of the intervention on educational attainment, their semester mean scores were analyzed through ANOVA (F = 8.244(2, 66), p≤0.001) where promising results were obtained. Conclusion: It was concluded that both interventions exerted meaningful effects on the attainment and distress of dorm-living students. Also, follow-up studies added proof on the permanence of the effects.